A public perception on sanitation and domestic waste management and reuse in Ho and its environs. - Ahorney, Edwin Setsoafia (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the Master of Science degree in Environmental Resources Management.